The Role of Ideology and Power in Systems Theory: Some Fundamental Shortcomings - Dimmock, Stuart; Sethi, Amarjit (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
This paper examines the presumption of stability within functionalist Systems theory by analyzing system theory's treatment of power and ideology in industrial relations and by comparing it with the writings of traditional and non-systems theorists.